Semantic differences between the vocabulary of Quran - حسين محيسن ختلان (College of Education for Women, 2019)
Ceremony of the Koran vocabulary animate different connotations unique style patch on smth not any method of Arabs, has been used used vocabulary and special Madza, he put every single in place of installation so that if you do not put in place misfire meaning and became Rkika method. Our goal in this research study a range of vocabulary in terms of the implications and documenting the trial of the Hadith and sayings of the beneficiaries of Arab scholars have different attitudes, linguists and interpreters and speakers and fundamentalists, philosophers, and others.